Novel Strategies for the Management of Recurrent Pregnancy Loss - Kutteh, William H. (Seminars in Reproductive Medicine, 2015)
This article discusses the current trends in the diagnosis and treatment of recurrent pregnancy loss. Genetic testing of the miscarriage tissue by 23-chromosome microarray and the ability to identify maternal cell contamination have increased our awareness of the role of aneuploidy as a cause of recurrent pregnancy loss. This increasing influence and the role of genetic testing in developing a strategy for the evaluation of recurrent pregnancy loss are described and discussed. The most common questions that practicing physicians ask about recurrent pregnancy loss include how many losses are needed to make the diagnosis, what counts as a pregnancy loss, what constitutes a full workup, should we get karyotypes on the parents and the miscarriage, and what is the prognosis for a live birth? This review attempts to answer those questions based on current research and clinical experience to expand our current understanding of recurrent pregnancy loss.
Keywords: recurrent pregnancy loss; antiphospholipid antibodies; uterine anomalies; recurrent miscarriage